Pengaruh Harga Kamar, Kualitas Pelayanan, dan Fasilitas Fisik Terhadap Tingkat Kepuasan Konsumen Pada The Cabin Hotel Ringroad Utara The Influence of Room Price, Service Quality, and Physical Facilities on Consumer Satisfaction Levels at The Cabin Hotel R - Putra, Novan Surya; Fuady, Misbach (EBBANK, 2024)
The Cabin Hotel North Ringroad is a service-oriented business offering comfortable accommodation to its customers. The purpose of this research is to analyze the effect of room price, service quality, and physical facilities on customer satisfaction with the addition of control variables. The research problem formulation is to assess whether the influence of each of these factors is statistically significant on the level of customer satisfaction or not. The population in this study consists of visitors who have used accommodation services at The Cabin Hotel North Ringroad, totaling 116 visitors. The sampling method in this research is accidental sampling technique. The analytical method used in this research is multiple linear regression analysis with the assistance of SPSS version 29.0. The results of this research state that, partially, the regression results indicate that price and physical facilities have a non-significant influence on customer satisfaction, while service quality has a significant influence on customer satisfaction. Furthermore, price, service quality, and physical facilities together have a significant influence on customer satisfaction. Additionally, the control variables, price, service quality, and physical facilities collectively have a significant impact on customer satisfaction. However, it should be noted that the addition of control variables resulted in a change in the F value from 125.333 to 97.059, indicating a decrease of 28.274. Nonetheless, it remains statistically significant